Improving Teacher Candidates' Lesson Planning Competencies Through Peer Review in a Wiki Environment. Issue 3 (2nd July 2016) - Salajan, Florin D.; Nyachwaya, James M.; Hoffman, Jeanette G.; Hill, Brent D.
Abstract : This article examines the implementation of a wiki-type platform for lesson planning for teacher candidates in an undergraduate general instructional methods course in the teacher education program of a Midwestern university in the United States. The study draws on the results of two separate sets of analysis involving 159 participants. Teacher candidates in this course were required to post the first five lesson plans of their unit plans to the course wiki. Each teacher candidate was required to analyze several classmates' lesson plans and provide constructive feedback that the authors of the lessons could incorporate in improving their unit plans. This exercise was meant to create a sense of constructive approach to lesson planning and encourage teacher candidates to think of their peers as resources to whom they could turn for advice in the process of designing lesson plans in an emerging community of practice, all while availing themselves of the flexibility of the wiki's collaborative features. Results show that teacher candidates improved their performance on lesson planning by incorporating feedback received via peer review in the wiki environment. In addition, the use of peer reviewing and lesson planning through the wiki informed most teacher candidates' intent to use the technology in some format in their future teaching practice .